2017
DOI: 10.1080/23120053.2017.1332800
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk perception and consistency in condom use among adolescents and young adults in urban Cape Town, South Africa: a cumulative risk analysis

Abstract: Background:The relationship between HIV risk perception and consistency in the use of condoms is scarcely understood in the context of a high HIV prevalence among adolescents and young adults in urban South Africa. Methods: Using data from Cape Area Panel Study (CAPS), gender-stratified analyses were conducted to determine relationship between risk perception and condom use among 14-22 year olds (n = 4 853) in urban Cape Town. Using discriminant function analyses, ecological determinants of consistency in cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…These findings concurred with other studies investigating the relationship between risk perception of acquring HIV and condom uptake which revealed that perceived risk for HIV infection had no significant impact on condom uptake (Muchiri, Odimengwu, & Wet, 2017;Stehr, 2006;Ashagrie, Tadesse, & Alebachew, 2016).They also resonated with the Harvard Mental Health Letter (2011)whichinformed us that risk perception was rarely entirely rational as people assessed risk through use of a mixture of cognitive skills by weighing the evidence and using reason and logic to reach a decision about risk.…”
Section: Discussion and Conclusion:-hiv And Aids Risk Perceptions Andsupporting
confidence: 91%
“…These findings concurred with other studies investigating the relationship between risk perception of acquring HIV and condom uptake which revealed that perceived risk for HIV infection had no significant impact on condom uptake (Muchiri, Odimengwu, & Wet, 2017;Stehr, 2006;Ashagrie, Tadesse, & Alebachew, 2016).They also resonated with the Harvard Mental Health Letter (2011)whichinformed us that risk perception was rarely entirely rational as people assessed risk through use of a mixture of cognitive skills by weighing the evidence and using reason and logic to reach a decision about risk.…”
Section: Discussion and Conclusion:-hiv And Aids Risk Perceptions Andsupporting
confidence: 91%
“…The association between more years of schooling and condom use has been reported by other studies [ 15 ]; however, it is unclear whether this association is driven by potential exposure to sexual education or other determinants influencing risky behaviors [ 29 ]. In this regard, previous evidence has shown that sex education in schools is linked to positive effects on the consistent and correct use of condoms and that there is a need for out-of-school programs aimed at providing relevant instructions before adolescent become sexually active [ 10 ].…”
Section: Discussionmentioning
confidence: 77%
“…Studies conducted in Cape Town, South Africa, have shown that adolescent substance use is correlated with poor physical health and mental health as well as delinquency. In terms of physical health, substance use in adolescence appears associated with risky sexual activity (Morojele & Ramsoomar, 2016; Muchiri, Odimegwu, & de Wet, 2017). This sexual risk behaviour elevates adolescents' risk of the acquisition of human immunodeficiency viruses (HIV), which is a major driver of the burden of disease in this country (Pillay‐van Wyk et al, 2016).…”
mentioning
confidence: 99%